Role of Social Organization Empowering Children - Koirala, Namita (Patan Pragya, 2020)
This research paper is a study on empowering children for being socio-economically independent by social organization. The primary purpose of this paper is to identify and analyze the prominent factors that have helped children to live their life independently. Moreover, this study attempts to explore whether there is any variation in children under 18who are living in social organization and children living with their own parents. It show show a social organization would help to empower children under age of 18, living with them for their future. For successful completion of the research, a quantitative and applied research methodology has been used in this study. The study reveals that how social organization helped for children being socio-economically independent; depends on skills and ability, uncovering the role of social organization for children sustainable lifestyle, methods and brain development learning’s and some convenient availability of informationand way of education.